Effects of Soluble Corn Fiber Alone or in Synbiotic Combination with Lactobacillus rhamnosus GG and the Pilus-Deficient Derivative GG-PB12 on Fecal Microbiota, Metabolism, and Markers of Immune Function: A Randomized, Double-Blind, Placebo-Controlled, Crossover Study in Healthy Elderly (Saimes Study) - Costabile, Adele; Bergillos-Meca, Triana; Rasinkangas, Pia; Korpela, Katri; de Vos, Willem M.; Gibson, Glenn R. (Frontiers in Immunology, 2017)
The aging process leads to a potential decline in immune function and adversely affects the gut microbiota. Dietary intervention is one approach to affect gut microbiota composition and improved functioning of the immune system. We investigated the effects of a probiotic Lactobacillus rhamnosus GG and pilus-deficient L. rhamnosus GG-PB12 combined with PromitorTM Soluble Corn Fibre (SCF, a candidate prebiotic) on faecal microbiota, metabolism, immunity and blood lipids in healthy elderly persons. A prospective, double-blind, placebo controlled, randomized, single centered, cross-over study in 40 healthy elderly subjects (aged 60-80 y) was carried out. Volunteers were randomized to consume either probiotic and prebiotic as synbiotic, prebiotic or placebo (maltodextrin) during 3-weeks. Three-week wash-out periods separated all the treatments. We assessed effects upon blood lipids, glucose, cytokines, NK cell activity, phenotype and intestinal microbiota composition. SCF decreased IL-6, which was not observed with the synbiotics. Consumption of L. rhamnosus GG combined with SCF increased NK cell activity compared to baseline in females and the older group. In the faecal microbiota analyses, the strongest community shifts were due to L. rhamnosus GG combined with SCF and SCF treatments. L. rhamnosus GG combined with SCF and L. rhamnosus GG-PB12 combined with SCF significantly increased the genus Parabacteroides. L. rhamnosus GG combined with SCF and SCF increased concentrations of Ruminococcaceae Incertae sedis. Oscillospira and Desulfovibrio slightly decreased in the L. rhamnosus GG combined with SCF group, whereas Desulfovibrio decreased also in the L. rhamnosus GG-PB12 combined with SCF group. L. rhamnosus GG combined with SCF reduced total cholesterol and LDL-cholesterol in volunteers with initially elevated concentrations. CRP significantly decreased during L. rhamnosus GG-PB12 combined with SCF intervention compared to baseline. Piliated L. rhamnosus GG was more potent at inducing beneficial effects compared to L. rhamnosus GG-PB12 by modulating the microbiome, increasing NK cell activity compared to SCF alone in older volunteers and decrease of the pro-inflammatory cytokine IL-6. The trial was registered at clinical-trial.gov as NCT03168503.